Population Dynamic of Scirtothrips dorsalis Hood (Thysanopetera: Thripidae) on Mango and Associated Weeds Under Low and Intensive Agricultural Practices - Affandi Affandi; Celia dela Rosa Medina; Luis Rey Ibanez Velasco; Pio Arestado Javier; Dinah Pura Tonelete Depositario; Ellina Mansyah; Hardiyanto Hardiyanto (AGRIVITA, Journal of Agricultural Science, 2019)
Population dynamic information and its influence factors are basic need for the best insect strategic control. This research objective was to descript and compare thrips S. dorsalis population dynamic on mango and associated weeds under low and intensive cultural practices. Reseacrh was conducted in PT. Trigatra Rajasa mango plantation in Ketowan, Arjasa, Situbondo, East Java, Indonesia from February 2014 to January 2015. The investigation was done through observation of S. dorsalis number associate on each mango growth stages and weeds under the canopy of mango. Arithmetic and descriptive method were applied to ensure the population oscillations pattern among phenological stages of mango and weeds under mango tree canopy. Result showed that population fluctuation of S. dorsalis was determined by growth stages of mango trees and the availability of initial built up of population. Flush growth stage was the most preferred stage which had high input agricultural practices such as fertilizer and tree conditioning and was supported for more numbers of thrips. Weeds Desmanthus leptophyllus, Achalypha indica, Azadirachta indica and Tephrosia vogelii were functioning as breeding habitat for early built-up population on mango trees. Climate factors especially rainfall was also affected population fluctuation of S. dorsalis on mango trees and weeds.